Development of Smart and Sustainable Economy in the European Union - Derlukiewicz, Niki (European Journal of Sustainable Development, 2014)
Innovations are very important in the development of the modern economy and are the major factor in proving the competitiveness of enterprises, as well as national and regional economies. Although the EU market is the one of the largest in the world, it is not sufficiently innovation-friendly. Currently Europe is facing many challenges associated for example with exhaustible natural resources, climate change, an aging population and increasing competition from the United States. Europe needs more investment in research and development to support the competitiveness of its industry and to improve its research and innovation system. Public and private investments in R&D are crucial to enable Europe to take advantage of any rebound in the economy. One of the European solutions to deal with these problems, is the new strategy dedicated to help socio-economic development of the European Union - Europe 2020. The new strategy for Europe 2020 emphasizes the need for member states to undertake joint action, which would help to overcome the crisis and implement reforms enabling them to face and deal with different problems. In order to achieve the above objectives some fundamental priorities were included in the strategy, i.e: smart and sustainable growth. The aim of this article is to present general guidelines for the development of smart and sustainable economy in the European Union in the context of current policy, strategic documents as well as activities and projects. Key words: smart, sustainable, development, strategy